The Basics of General Financial Science by Antun Ferdinand Albely. Knowledge Circulation and Digital Text Analysis of a Legal Textbook - Novosel, Zrinko (Review of Croatian History, 2023)
This paper aims to present interpretations and modifications of the early 19th century legal and economic knowledge within A. F. Albely's The Basics of General Financial Science, a textbook which focuses on the aspect of public finances. Referencing his own work to other authors in this academic field, Albely participated in a disciplinary discourse which served as a hub for circulation of ideas. This paper's primary concern is revealing the sources of Albely's legal and economic knowledge and noticing modifications which occured in ideas between different texts. Digital text analysis, accessed at the web-available platform Voyant tools, will prove to be an important heuristic asset, as it will disclose textual environments of ideas appearing in the analysed texts. This approach will enable new interpretative possibilities in the investigative field of knowledge circulation, as it will employ results of digital text analysis in order to discern Albely's intellectual influences and give insight into an idea modification process.